Lead extraction for reduction of chronic pain related to cardiovascular implantable electronic device. Issue 5 (28th January 2019) - Lewis, Kathryn; Dai, Mingyan; Patton, Kristen K; Cha, Yong-Mei; Pollema, Travis; Feld, Gregory K; Birgersdotter-Green, Ulrika; Pretorius, Victor
Abstract: Aims: Chronic pain at the cardiovascular implantable electronic device (CIED) generator or lead insertion site that is not otherwise manageable carries a IIA indication for extraction. However, limited data exist evaluating causes of pain and outcomes of extraction in eliminating pain. A multi-centre retrospective observational study was conducted to evaluate outcomes of patients undergoing device extraction for treatment of chronic device pain. Methods and results: Twenty-seven out of 2188 lead extraction candidates (1.3%) met the chronic pain IIA indication for extraction [50 ± 16 years; 14 (51%) women]. Onset, severity, triggers, and pain management were measured before and after extraction. Device type, procedure done (with/without reimplantation), and positive tissue cultures were noted. Pain was reported as constant ( n  = 14; 50%), intermittent ( n  = 13; 46%), and movement-triggered ( n  = 14; 50%). Average severity of pain was seven out of 10 (10 being the worst). Post-extraction, 18 (66%) received freedom from pain, including all patients with poorly formed pockets ( n  = 2) and subclinical infections ( n  = 2). Of the 18, 11 underwent reimplantation (61%) without recurrent pain. Nine still had pain (44 ± 17 years; seven women) after extraction. Eight of the nine underwent reimplantation, three on the contralateral chest wall and five ipsilaterally. Pain severity decreased ( n  = 5), increased ( n  = 1), or was unchanged ( n  = 3). Conclusion: Chronic pain at the CIED generator site can present as chronic or movement-triggered pain, and can be due to subclinical infection or a poorly formed device pocket. Extraction relieved constant and intermittent pain in two-thirds of patients. Extraction appears less successful in eliminating pain in women who undergo subsequent reimplantation.